MODERNISME PEMBELAJARAN BAHASA ARAB BERBASIS PESANTREN DI RANGKASBITUNG BANTEN - Rozak, Abd (IMLA (Arabic Teacher and Lecturer Association of Indonesia), 2018)
This study aimed to analyze the strengths, weaknesses, opportunities, and challenges in learning Arabic in traditional and modern Islamic boarding schools (pesantren) in Lebak Regency, Banten. This was a qualitative research. The researcher directly reviewed the curriculum and learning documentsand observed learning Arabic at both pesantrens. The ongoing learning was studied, understood, described, analyzed, and criticized. The results showed that the education system of modern pesantren was more open to study contemporary books in addition to classical books with the main target of being fluent in Arabic (maharah al-kalam). One of the distinctive characteristics of modern pesantren is that the languages spoken by all elements of this institution are Arabic and English as an attempt to meet the challenges in the era of globalization.